Mekanisme probiotik lactobacillus plantarum dalam sistem imun pada penderita diare - Afifah, Nadia (Wellness And Healthy Magazine, 2020)
Probiotics are defined as living microorganisms which, when consumed in sufficient quantities, can provide health benefits. Lactobacillus Plantarum and Lactobacillus acidophilus include probiotics. Probiotics can protect the digestive tract from adhesion to pathogenic bacteria. Diarrhea is a disease characterized by increasing the frequency of bowel movements more than 3-4 days. The cause of diarrhea can be in the form of infections (bacteria, viruses, parasites), food poisoning, drug use, and others. Diarrhea can also occur due to physiological changes such as: (1) increased intraluminal osmolarity, (2) increased fluid and electrolyte secretion, (3) presence of infectious agents in the intestinal wall. The management of the World Health Organization (WHO) is rehydration (ORS fluids), diet, zinc, selective antibiotics, and education to parents of patients. But lately, probiotics have been proven to accelerate the healing process of diarrhea patients. There are emat mechanisms in the immune system process for patients with first diarrhea, preventing adhesion of pathogenic bacteria to the intestinal epithelium, both improving the function of the intestinal epithelium, the therapeutic effect of L. Plantarum will prevent bacteria from passing through the parasellular and transepithelial (transcellular) pathways to tissues outside the intestine, third inhibits pro-inflammatory cytokines, fourth induces immunoglobulin A (IgA)